Complex dynamics of glass-forming liquids a mode-coupling theory - d (Oxford : Oxford University Press, 2009)
Amorphous condensed matter can exhibit complex motions on time scales which extend up to those relevant for the functioning of biomaterials. The book presents the derivation of a microscopic theory for amorphous matter, which exhibits the evolution of such complex motions as a new paradigm of strongly interacting particle systems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Viscosity; Mode-coupling theory; Equations of motion; Complex fluids; Molecular dynamics